Pengaruh Model Discovery Learning Berbantuan Media Konkret Tangram Terhadap Kemampuan Berpikir Kreatif Matematis Siswa Sekolah Dasar - Kinanti Dilla Putri; Sofyan Iskandar; Teten Ginanjar Rahayu (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the effect of the Discovery Learning model assisted by Tangram concrete media on the mathematical creative thinking skills of fourth-grade elementary school students and to compare its effectiveness with the STAD cooperative learning model assisted by PowerPoint. This research used a quasi-experimental method with a non-equivalent control group design involving 50 fourth-grade students of SDN Lubang Buaya 02 Setu, Bekasi Regency, in the 2025/2026 academic year. The experimental class received Discovery Learning assisted by Tangram, while the control class received STAD assisted by PowerPoint. Data were collected using eight validated essay questions measuring fluency, flexibility, originality, and elaboration. The data were analyzed using simple linear regression, paired sample t-test, independent sample t-test, and N-Gain analysis. The results showed that Discovery Learning assisted by Tangram had a significant effect of 49.7% on students' mathematical creative thinking skills and was more effective than STAD assisted by PowerPoint. Thus, Discovery Learning assisted by Tangram can be used as an alternative model to improve students' mathematical creative thinking skills in learning plane figure material.